On the development of an intelligent blender for household and commercial food processing - Mujibur Rahman, Kazi; Salami, Momoh Jimoh Eyiomika; Martono, Wahyudi; Albagul, Abdulgani; Zainudin, Fadzilah; Khan, Md. Raisuddin (2006)
Blending machines are one of the most essential items for food processing in homes and restaurants. Most of the available blenders nowadays are conventional and use manual control requiring full time supervision and also need user expertise for efficient operation. In these machines, AC series motors are mostly used because blending needs high speed operation. The starting current is excessively high over a prolonged period causing voltage dip and injecting low order harmonics in the power line, thereby degrading the power quality of neighboring users. In this research work, an intelligent external controller is proposed that can control the starting current as well as operating strategy. To make the controller more economic, a new control strategy is adopted where the user chooses the food staff, amount and the type of operation. An intelligent program is embedded in the controller that decides the speed and time of operation. The controller is designed with low cost AT89C52 microcontroller along with PWM power interface for driving the ac series motor.